2007
DOI: 10.4012/dmj.26.915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Characteristics on Adherence of S. mutans Biofilms to Indirect Resin Composites

Abstract: The purpose of this study was to evaluate the adherence of biofilms to the surfaces of two indirect resin composites, Estenia C&B and Gradia. Slabs were prepared from the materials, and then either ground with 800-grit silicon carbide paper or polished with diamond pastes up to 1 μm. Artificial biofilms of Streptococcus mutans were grown on the composite slabs in an artificial mouth system for 20 hours. Thereafter, the amounts of retained biofilm on the surfaces were measured after sonication. Surface characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 40 publications
8
59
1
5
Order By: Relevance
“…These results are supported by previous studies showing that surface roughness as well as composition of the resin composites (filler size and matrix monomer) influence biofilm formation 3,24,45,47) . Filled resins (composites) and particularly DMA (organic composites) display several features.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These results are supported by previous studies showing that surface roughness as well as composition of the resin composites (filler size and matrix monomer) influence biofilm formation 3,24,45,47) . Filled resins (composites) and particularly DMA (organic composites) display several features.…”
Section: Discussionsupporting
confidence: 81%
“…Other investigators state that polished composite surfaces supported larger amounts of plaque due to the loss of superficial filler particles during the polishing process 4,25,50,52) . These observations contradict those of other authors who found that surface polishing of composite materials rendered the materials more plaque resistant and that the procedure was important to reduce bacterial accumulation 8,37,45) . The use of air-polishing devices in oral hygiene and periodontal therapy has proven to be a very effective means in rapidly removing stains and dental plaque 10) .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…7,8 AMS model consisted of two transparent tubes made of glass with a diameter of 10 cm. The first tube was used to accommodate BHI broth as a nutrient medium for bacteria, while the second tube kept RK samples in anaerobic state and also avoided RK samples from contamination.…”
Section: Methodsmentioning
confidence: 99%